OPTIMALISASI PERAN KELUARGA DALAM PENCEGAHAN STUNTING MELALUI PELATIHAN SENAM BAYI - Retno Setyo Iswati; Desta Ayu Cahya Rosyida (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The baby has infants who experience delays in development will make parents feel anxious and worried. So the baby has difficulty walking and lacks language; the lack of stimulation provided to the baby will worsen developmental delays in infants (Hurlock, 2002). The number of children under five in Siwalankerto Sub-District, Wonocolo District, Surabaya City, is quite large. The solution offered to this problem is to do baby gymnastics training for infants aged more than 3 months. With baby exercises provide touch stimulation, which believed to have been very beneficial for babies. Baby gymnastics used to help stimulate the growth and development of the nervous and motor system in healthy and normal infants in the phase of development according to age and ability. This activity can optimize gross motor skills, improve coordination, concentration, the balance of body movements and increase baby's physical strength, also through gymnastics baby closeness (bonding) between mother and baby will be more reliable. Counseling activities, as well as demonstrations of Baby Gymnastics To stimulate growth and development, more optimal babies, improve baby's sensory and motor skills. Then Increase the mother's knowledge about the importance of applying baby exercises to the child.